Fixed-time terminal sliding mode tracking protocol design for high-order multiagent systems with directed communication topology - Ni, Junkang (ISA transactions, 2022)
This paper presents a novel fixed-time consensus tracking protocol for high order multi-agent system (MAS) with directed communication topology. A new distributed observer is proposed such that fixed-time leader’s state estimation can be achieved, which overcomes the difficulty arising from asymmetry of communication topology. A series of terminal sliding surfaces are constructed and a singularity-free sliding mode fixed-time tracking protocol is developed. It is proved that the proposed tracking protocol achieves fixed-time consensus tracking. Particularly, we can obtain the controller gain from the pre-specified time, which helps to tune the gain in accordance with consensus time requirement. Moreover, a less conservative convergence time bound estimation is attained. Simulation examples demonstrate the effectiveness of the presented scheme.